Enhancing English reading motivation and performance via the ARCS model: an empirical study using the ARCS motivation scale - Wang, Zhonger; Lu, Jin; Yu, Shenchen (Frontiers in Psychology, 2025)
The ARCS motivation model comprises four factors: Attention, Relevance, Confidence, and Satisfaction. This study aims to investigate the effectiveness of the teaching approach based on this model in English reading for Chinese university students. Two classes of 80 sophomores participated in the experiment, with 40 in the experimental group and 40 in the control group. The experimental group received ARCS-based instruction, while the control group followed the traditional grammar-translation method over a four-month teaching session. A survey, which included the four factors derived from exploratory and confirmatory factor analysis, was conducted among 611 university students before and after the experiment to explore the English reading motivation of the two classes of students in four dimensions. Also, the research team administered two English reading tests of the same difficulty level to assess students’ reading ability before and after the experiment. The results of the data analysis showed that using an independent-sample t-test, there was a statistically significant increase in the total reading motivation level and a rise in the four dimensions for the students in the experimental group who received instruction based on the ARCS model. Additionally, when the researchers retested the total English reading scores of the experimental group using independent-samples t tests again, the total English reading scores of the experimental group increased significantly. Furthermore, all four factors were significantly correlated with English reading achievement, with Confidence and Satisfaction playing important roles in predicting their reading proficiency. The study concludes by outlining measures to improve the ARCS-based instructional approach.